2016
DOI: 10.1097/md.0000000000005097
|View full text |Cite
|
Sign up to set email alerts
|

From biportal to uniportal video-assisted thoracoscopic anatomical lung resection

Abstract: Our study sought to review our experience from biportal to uniportal video-assisted thoracoscopic surgery (VATS) major lung resection. Lessons we learned from the evolution regarding technical aspects were also discussed.We retrospectively reviewed patients who underwent VATS lobectomy or segmentectomies in Ditmanson Medical Foundation Chia-Yi Christian Hospital, Chia-Yi, Taiwan, during January 2012 and December 2014. Patient clinical profiles, surgical indications and procedures, postoperative course, and onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Five patients underwent uniportal anatomic sublobar resections performed by an experienced surgeon in very high volume institutions (12). The diagnose leading to these procedures went from solitary or multiple GGO nodules to solid lesions involving the fissure in patients who did not endure pneumonectomy.…”
Section: Patients and Workupmentioning
confidence: 99%
“…Five patients underwent uniportal anatomic sublobar resections performed by an experienced surgeon in very high volume institutions (12). The diagnose leading to these procedures went from solitary or multiple GGO nodules to solid lesions involving the fissure in patients who did not endure pneumonectomy.…”
Section: Patients and Workupmentioning
confidence: 99%
“…After removing duplicates, irrelevant articles, case reports, letters, reviews, comments or meta-analyses, 15 references were identified and assessed further by screening the full texts. After the exclusion of four studies which did not provide the appropriate data, 11 studies (2)(3)(4)(5)7,8,(12)(13)(14)(15)(16) were included for final assessment and were deemed to be suitable for quantitative meta-analysis. The process of article selection is summarized in Figure 1.…”
Section: Selection Processmentioning
confidence: 99%
“…Also, other potential advantages have been reported, including a significant reduction of postoperative pain (2,3), a shorter hospital stays (4,5) as well as improved patient satisfaction (6). Therefore, there was a hypothesis that uniport VATS might be superior to multiport VATS.…”
Section: Introductionmentioning
confidence: 99%
“…The pursuit for mini-invasive keeps promoting the evolution of VATS from traditional multipleport to single-port for most VATS resections, and with the progress of VATS experience, UVATS has become technically feasible to perform lung resections. When compared with traditional multiple-port VATS, UVATS was found to result in equivalent perioperative outcomes and reduced postoperative pain and discomfort [15]. Despite these advancements and the popularization of the UVATS technique, lung resection for PS remains a prohibited area.…”
Section: Introductionmentioning
confidence: 99%